Xiaoaiping Induces Developmental Toxicity in Zebrafish Embryos Through Activation of ER Stress, Apoptosis and the Wnt Pathway - Li, Juanjuan; Zhang, Yun; Liu, Kechun; He, Qiuxia; Sun, Chen; Han, Jian; Han, Liwen; Tian, Qingping (Frontiers in Pharmacology, 2018)
The aim of the study was to determine the developmental toxicity of the traditional Chinese medicine Xiaoaiping (XAP) and to investigate its underlying mechanism of action. Zebrafish embryos were incubated with 0.4, 0.8, 1.2 and 1.6 mg/mL XAP. Endpoints such as mortality, hatching rate, malformation, body length, morphology score, swimming behaviour, histological changes, reactive oxygen species (ROS) production, total superoxide dismutase (T-SOD) activity, and the mRNA expression of genes related to oxidative stress, endoplasmic reticulum (ER) stress, apoptosis and the Wnt pathway were evaluated. Our results demonstrated that XAP exposure increased mortality and malformation and reduced the hatching rate. XAP resulted in severe malformation, including swim bladder deficiency, yolk retention, pericardial edema, and tail curvature. Histopathological analysis showed that XAP induced liver, heart and muscle injury. High doses (≥1.2 mg/mL) of XAP notably decreased the locomotor capacity of zebrafish. ROS generation was remarkably increased and T-SOD activity was decreased, confirming that oxidative stress was induced by XAP. The mRNA expression levels of ER stress-related genes (chop, hspa5, hsp90b1 and perk), apoptosis-related genes (caspase-3, bax and p53) and wnt11 were significantly upregulated by XAP exposure. The expression levels of the oxidative stress-related genes (cat, sod1 and gstp2), Wnt pathway-related genes (β-catenin, wnt3a and wnt8a) and bcl-2 initially increased and then decreased as the XAP exposure dose increased. In conclusion, we provide evidence for the first time that XAP can induce dose-related developmental toxicity, and ER stress, apoptosis and the Wnt pathway participate in the toxicity regulation.